(untitled) - Kulakovskaya, Ekaterina (New York, 2014)
Extracellular Glycolipids of Yeasts: Biodiversity, Biochemistry, and Prospects provides a comprehensive view of the biochemistry, biological activity, and practical application of extracellular glycolipids of yeast. This book brings much-needed clarity to the complex topic of glycolipids and streamlines the rather confusing terminology used for glycolipids. It also provides a wealth of modern data on their composition, structure and properties, biosynthetic pathways, methods of isolation and identification, antifungal activity, and mechanisms of action.
Keywords: Yeast fungi.,Nấm men,Glycolipids,Glycolipids; Analysis,Phân tích